Are Nutritional Guidelines Followed in the Pediatric Intensive Care Unit? - Mylène Jouancastay; Camille Guillot; François Machuron; Alain Duhamel; Alain Duhamel; Jean-Benoit Baudelet; Stéphane Leteurtre; Stéphane Leteurtre; Morgan Recher; Morgan Recher (Frontiers Media S.A., 2021)
Background: French (2014) and American (2017) pediatric guidelines recommend starting enteral nutrition (EN) early in pediatric intensive care. The aims of this study were to compare the applicability of the guidelines in the pediatric intensive care unit (PICU) and to identify risk factors of non-application of the guidelines.Methods: This retrospective, single-center study was conducted in a medical-surgical PICU between 2014 and 2016. All patients from 1 month to 18 years old with a length of stay >48 h and an exclusive EN at least 1 day during the PICU stay were included. The outcome variable was application of the 2014 and 2017 guidelines, defined by energy intakes ≥90% of the recommended intake at least 1 day as defined by both guidelines. The risk factors of non-application were studied comparing "optimal EN" vs. "non-optimal EN" groups for both guidelines.Results: In total, 416 children were included (mortality rate, 8%). Malnutrition occurred in 36% of cases. The mean energy intake was 34 ± 30.3 kcal kg−1 day−1. The 2014 and 2017 guidelines were applied in 183 (44%) and 296 (71%) patients, respectively (p < 0.05). Following the 2017 guidelines, enteral energy intakes were considered as "satisfactory enteral intake" for 335 patients (81%). Hemodynamic failure was a risk factor of the non-application of both guidelines.Conclusion: In our PICU, the received energy intake approached the level of intake recommended by the American 2017 guidelines, which used the predictive Schofield equations and seem more useful and applicable than the higher recommendations of the 2014 guidelines. Multicenter studies to validate the pediatric guidelines seem necessary.